2005
DOI: 10.1007/s10593-005-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of heterocyclic compounds at the Department of Organic Chemistry, Chemical Faculty, M. V. Lomonosov State University. (Review)

Abstract: This review of achievements in the area of the chemistry of heterocyclic compounds at the Department of Organic Chemistry of M. V. Lomonosov Moscow State University is dedicated to the 250th anniversary of the University and the 75th anniversary of the Chemical Faculty. It contains a brief historical account and information on researches carried out by the team at the Department in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 105 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…If we compare the reproduction of shrubs with seeds and vegetative ways in order to increase the yield of Mulberry, then in the first years of use, it is possible to make sure that in the first case, the increase in productivity is different in different environments. While it is possible to observe that the Leaf yield growth in the Bush mulberry, which is grown from Sprouts, is very sluggish, while in the Bush mulberry, which has its own roots, it was observed that the use of the Leaf sharply increases the yield in the second year, in other words, the yield of the second year leaf from the In the Bush mulberries with an acre root, the range of plants in the range of 3 meters in a row was 0,5 meters, while the number of Bush mulberries in each hectare was 3700 units, in the second year after planting from cuttings in the first year of using mulberry leaves, the yield of leaves per hectare was 2,8 -3,0 tons, It can be seen that in the third year of use of mulberries, the Leaf yield obtained from Mulberry was observed in the fourth year in a permanent place in the seed -recovered mulberries, the mass of the Leaf was 2 -3 tons more than in the first year, which indicates that the yield was 2,0-2,5 times higher than the [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…If we compare the reproduction of shrubs with seeds and vegetative ways in order to increase the yield of Mulberry, then in the first years of use, it is possible to make sure that in the first case, the increase in productivity is different in different environments. While it is possible to observe that the Leaf yield growth in the Bush mulberry, which is grown from Sprouts, is very sluggish, while in the Bush mulberry, which has its own roots, it was observed that the use of the Leaf sharply increases the yield in the second year, in other words, the yield of the second year leaf from the In the Bush mulberries with an acre root, the range of plants in the range of 3 meters in a row was 0,5 meters, while the number of Bush mulberries in each hectare was 3700 units, in the second year after planting from cuttings in the first year of using mulberry leaves, the yield of leaves per hectare was 2,8 -3,0 tons, It can be seen that in the third year of use of mulberries, the Leaf yield obtained from Mulberry was observed in the fourth year in a permanent place in the seed -recovered mulberries, the mass of the Leaf was 2 -3 tons more than in the first year, which indicates that the yield was 2,0-2,5 times higher than the [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%